Involvement of Arterial Baroreflex in the Protective Effect of Dietary Restriction Against Stroke. Issue 6 (June 2013) - Liu, Ai-Jun; Guo, Jin-Min; Liu, Wei; Su, Feng-Yun; Zhai, Qi-Wei; Mehta, Jawahar L; Wang, Wei-Zhong; Su, Ding-Feng
Dietary restriction (DR) protects against neuronal dysfunction and degeneration, and reduces the risk of ischemic stroke. This study examined the role of silent information regulator T1 (SIRT1) and arterial baroreflex in the beneficial effects of DR against stroke, using two distinct stroke models: stroke-prone spontaneously hypertensive rats (SP-SHRs) and Sprague-Dawley (SD) rats with middle cerebral artery occlusion (MCAO). Sirt1 knockout (KO) mice were used to examine the involvement of sirt1 . Sinoaortic denervation was used to inactivate arterial baroreflex. Dietary restriction was defined as 40% reduction of dietary intake. Briefly, DR prolonged the life span of SP-SHRs and reduced the infarct size induced by MCAO. Dietary restriction also improved the function arterial baroreflex, decreased the release of proinflammatory cytokines, and reduced end-organ damage. The beneficial effect of DR on stroke was markedly attenuated by blunting arterial baroreflex. Lastly, the infarct area in sirt1 KO mice was significantly larger than in the wild-type mice. However, the beneficial effect of DR against ischemic injury was still apparent in sirt1 KO mice. Accordingly, arterial baroreflex, but not sirt1, is important in the protective effect of DR against stroke.